2008
DOI: 10.1002/hipo.20456
|View full text |Cite
|
Sign up to set email alerts
|

Multiple repetitions reveal functionally and anatomically distinct patterns of hippocampal activity during continuous recognition memory

Abstract: We used a continuous recognition procedure that included multiple presentations of test items, along with high-resolution functional magnetic resonance imaging (fMRI), to investigate the relationship between item novelty and recognition-related activity in the medial temporal lobe (MTL). In several regions of hippocampus and parahippocampal cortex, activity elicited by new items exceeded that for old items, whereas no MTL regions exhibited greater activity for old items. Critically, anatomically-distinct regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
75
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 37 publications
21
75
0
Order By: Relevance
“…Past studies have found direct neuronal activity between the medial prefrontal cortex and the hippocampus in rodents during spatial working memory tasks (Jones and Wilson, 2005;Siapas et al, 2005) and there is evidence for a fronto-parietal network (Laufs, 2008;van den Heuvel et al, 2009). One major effect of the parahippocampal activation might be the updating of the working memory processes, as this region is wellknown for its role in episodic memory (Johnson et al, 2008;Kumari et al, 2003;Ramsoy et al, 2009). Reciprocal connections between the dorsolateral prefrontal cortex (including the ACC) and the parahippocampal region are known (Goldman-Rakic et al, 1984).…”
Section: N-back Erp Study Resultsmentioning
confidence: 99%
“…Past studies have found direct neuronal activity between the medial prefrontal cortex and the hippocampus in rodents during spatial working memory tasks (Jones and Wilson, 2005;Siapas et al, 2005) and there is evidence for a fronto-parietal network (Laufs, 2008;van den Heuvel et al, 2009). One major effect of the parahippocampal activation might be the updating of the working memory processes, as this region is wellknown for its role in episodic memory (Johnson et al, 2008;Kumari et al, 2003;Ramsoy et al, 2009). Reciprocal connections between the dorsolateral prefrontal cortex (including the ACC) and the parahippocampal region are known (Goldman-Rakic et al, 1984).…”
Section: N-back Erp Study Resultsmentioning
confidence: 99%
“…There is some evidence for experience-dependent differences in rodent hippocampal activity that are manifest by electrophysiological differences in individual or ensemble neuronal activity patterns (Otto and Eichenbaum 1992;Fyhn et al 2002;Nitz and McNaughton 2004). Neuroimaging studies in humans have detected increased fMRI activity in the hippocampal region during encoding of novel visual stimuli (Stern et al 1996;Johnson et al 2008). Moreover, humans with hippocampal damage exhibit altered event-related potentials in response to novel stimuli (Knight 1996).…”
mentioning
confidence: 99%
“…The memory strength account of hippocampal activity has been challenged recently by the results of fMRI studies using the continuous recognition procedure (e.g., Suzuki et al, 2011;Johnson, Muftuler, & Rugg, 2008). According to these authors, if hippocampal activity reflects strong memories rather than recollection of contextual details associated with an item, then it should demonstrate a positive correlation with item repetition during continuous recognition.…”
Section: Repetition In Item Versus Continuous Recognitionmentioning
confidence: 99%
“…A number of authors have noted the likelihood of concurrent encoding of new and repeated items during continuous recognition (e.g., Johnson et al, 2008;Yassa & Stark, 2008;Brozinsky, Yonelinas, Kroll, & Ranganath, 2005). Johnson et al (2008) interpreted the reductions in hippocampal activity observed with successive item presentation in their study as reflecting "new item encoding" that "likely played a minimal (if any) role in supporting recognition judgments." To make judgments about serial order in continuous recognition (e.g., Suzuki et al, 2011), participants need to encode temporal information, a requirement that is absent during typical retrieval tasks in item recognition memory.…”
Section: Repetition In Item Versus Continuous Recognitionmentioning
confidence: 99%